Social and personality development : an advanced textbook - Lamb, Michael E., 1953-; Bornstein, Marc H. (New York, NY : Psychology Press, 2011)
This text contains parts of Bornstein and Lamb's Developmental Science, 6th edition, along with new introductory material, providing a cutting edge and comprehensive overview of social and personality development. Each of the world-renowned contributors masterfully introduces the history and systems, methodologies, and measurement and analytic techniques used to understand the area of human development under review. The relevance of the field is illustrated through engaging applications. Each chapter reflects the current state of knowledge and features an introduction, an overview of the field, a chapter summary, and numerous classical and contemporary references. As a whole, this highly anticipated text illuminates substantive phenomena in social and personality developmental science and its relevance to everyday life.
Includes bibliographical references and index.
Keywords: Developmental psychology; Personality development